UUM targets 10% lecturers with PhDs by 2020 - New Sabah Times English, (KK) (New Sabah Times English (KK), 2012)
SINTOK: Universiti Utara Malaysia (UUM) is targeting to have 10 per cent of its 1,200 lecturers holding Doctor of Philosophy (PhD) degrees and be one of the world's top 100 universities by 2020.